Pengembangan Digitalisasi Pemasaran UMKM Pada Kelompok Pengolah dan Pemasar Ikan Waluya Kota Bandar Lampung - Dicky Rizky Ramadhan Effendi; Mutiara Aziza Ramadhani; Surya Baskara Saputra; Annisa Citra Wulandari; Ikhwan Victhori; Mahrinasari Mahrinasari; Roslina Roslina (I-Com: Indonesian Community Journal, 2024)
Digital marketing channels can be done by utilizing social media and e-commerce. The presence of social media is very important and needed, including being able to use it to improve business by promoting its products, especially for small businesses or Micro, Small and Medium Enterprises (MSMEs). Marketing and sales that still use conventional methods is the main problem that the government has paid attention to so that MSMEs reach a wider market, where there are still many MSMEs that do not use the internet for their business through social media or eCommerce. Participants in this activity are MSMEs, anchovy craftsmen, Pulau Pasaran Province. Lampung which is called the Waluya Fish Processing and Marketing Group (Poklahsar). This activity was attended by 6 participants consisting of the chairman and core team of the business group who were actively involved in business development. This activity uses the Community-Centered Development (CCD) method with stages of preparation, socialization, CCD and mentoring. The results of the activity showed that participants were able to create interesting content independently and interestingly (Facebook, Instagram and TikTok). The successful development of MSME Marketing Digitalization also requires support from the Government's role in continuing to provide development and marketing education, especially product advertising, to increase social media account traffic more quickly.